Intestinal permeability in type 1 diabetes: An updated comprehensive overview. Issue 122 (August 2021) - Mønsted, Mia Øgaard; Falck, Nora Dakini; Pedersen, Kristina; Buschard, Karsten; Holm, Laurits Juulskov; Haupt-Jorgensen, Martin
Abstract: The etiopathogenesis of the autoimmune disease type 1 diabetes (T1D) is still largely unknown, however, both genetic and environmental factors contribute to the development of the disease. A major contact surface for environmental factors is the gastrointestinal (GI) tract, where barrier defects in T1D likely cause diabetogenic antigens to enter the body tissues, contributing to beta-cell autoimmunity. Human and animal research imply that increased intestinal permeability is an important disease determinant, although the underlying methodologies, interpretations and conclusions are diverse. In this review, an updated comprehensive overview on intestinal permeability in patients with T1D and animal models of T1D is provided in the categories: in vivo permeability, ex vivo permeability, zonulin, molecular permeability and blood markers. Across categories, there is consistency pointing towards increased intestinal permeability in T1D. In animal models of T1D, the intestinal permeability varies with age and strains implying a need for careful selection of method and experimental setup. Furthermore, dietary interventions that affect diabetes incidence in animal models does also impact the intestinal permeability, suggesting an association between increased intestinal permeability and T1D development. Highlights: Small intestinal paracellular permeability is increased in type 1 diabetes. Various methods can be used to evaluate intestinal permeability. Intestinal permeability and diabetes incidence can be modified by diet. Molecular markers of intestinal permeability are difficult to interpret.